Covalent organic framework/carbon black/molecularly imprinted polydopamine composites for the selective recognition and electrochemical detection of ciprofloxacin - Yufeng Sun; Yongfeng Chen; Xiaomin Pang; Geoffrey I.N. Waterhouse; Xuguang Qiao; Zhixiang Xu (Food Science and Human Wellness)
In this work, a novel electrochemical sensor based on covalent organic framework@carbon black@molecularly imprinted polydopamine (COF@CB@MPDA) was developed for selective recognition and determination of ciprofloxacin (CF). COF@CB@MPDA possessed good water dispersibility and was synthesized by the self-polymerization of dopamine under alkaline conditions in the presence of the COF, CB and CF. The high surface area COF enhanced the adsorption of CF, whilst CB gave the composites high electrical conductivity to improve the sensitivity of the proposed COF@CB@MPDA/glassy carbon electrode (GCE) sensor. The specific recognition of CF by COF@CB@MPDA involved hydrogen bonding and van der Waals interactions. Under optimized conditions, the sensor showed a good linear relationship with CF concentration over the range of 5.0 × 10–7 and 1.0 × 10–4 mol/L, with a limit of detection (LOD) of 9.53 × 10–8 mol/L. Further, the developed sensor exhibited high selectivity, repeatability and stability for CF detection in milk and milk powders. The method used to fabricate the COF@CB@MPDA/GCE sensor could be easily adapted for the selective recognition and detection of other antibacterial agents and organic pollutants in the environment.